Interdisciplinary Oral Nutrition Support and Supplementation After Hip Fracture Surgery in Older Adult Inpatients: A Global Cross-Sectional Survey (ONS-STUDY) - Jack Bell; Ruqayyah Turabi; Sissel Urke Olsen; Katie Jane Sheehan; Ólöf Guðný Geirsdóttir (2025)
Malnutrition predicts poor outcomes following hip fracture, affecting patient recovery, healthcare performance, and costs. Evidence-based guidelines recommend multicomponent, interdisciplinary nutrition care to improve intake, reduce complications, and enhance outcomes. This study examines global variation in oral nutrition support for older (65+ years) hip fracture inpatients. A global survey was conducted as part of a broader program to improve interdisciplinary nutrition care. The protocol was based on evidence-based guidelines, reviewed by experts, and piloted for validity. Recruitment used snowball sampling to achieve diversity across income levels, countries, and healthcare roles. The survey (July-September 2023) recruited 308 participants from 46 countries across five global regions. Respondents primarily worked in acute teaching (57.5%) and non-teaching (17.5%) hospitals, representing medical (48.4%), nursing (28.2%), and allied health (17.9%) roles. Findings revealed a global knowledge-to-practice gap in multicomponent nutrition care, across providing high-protein/energy food and fluids (median: "half the time"), post-operative provision of oral nutritional supplements (median: "half the time") and continuation for one month with assessment (median: "not very often"), and nutritional education (median: "not very often"). Only 17.9% of respondents reported routine provision ("often" and "nearly always or always") of high-protein/energy food, supplements, and education. Substantial regional variation showed Western Pacific respondents perceiving the lowest provision across multicomponent processes. Interdisciplinary, multicomponent interventions were seen as a potential opportunity requiring further exploration. Major gaps persist in implementing evidence-based, interdisciplinary, multicomponent nutrition care for older adults with hip fractures. A targeted implementation approach is the next step to addressing the knowledge-to-practice gap.